Politeness And Intercultural Pragmatics Perspective In WhatsApp Group Of Student Boarding House In Yogyakarta (ELS Journal on Interdisciplinary Studies in Humanities, 2025)
This study examines multicultural communication politeness strategies in online interactions of WhatsApp Group boarding female students in Tamanan, Yogyakarta. This research uses the theory of politeness from Brown & Levinson and intercultural pragmatics from Kecskes. The method used in this research is qualitative. The object of this research is the chat in the WhatsApp Group in 2024-2025. The results show that, first, the dominant politeness strategy is negative politeness with a percentage of 42.86%, positive politeness with a percentage of 31.43%, off record with a percentage of 14.29%, and bald-on record with a percentage of 11.43%. The findings show that speakers always package reprimands, requests, and orders with politeness substrategies such as apologies, the use of the word please, solidarity markers, indirectness, giving reasons, and innuendo. Second, the power factor lies with the boarding owner, so the boarders must be more polite. The distance between the owner and boarders is close, while the distance between boarders is quite close; it is influenced by direct interaction, social status, and gender. Ranking of imposition is always played with greetings, apologies/help, core speech, and reasons. Third, CCG is diverse but still prioritises politeness, thus creating an ECG that regulates new habits. Different egocentrism, but the same style of polite speech, so that it can be accepted together (cooperation). Then, hybrid norms that are inclusive strengthen solidarity and cooperation. Despite coming from different cultural backgrounds, the speakers still prioritise Indonesian society's general politeness, which is indirect, collective, and accommodating to Javanese culture.
Keywords: Politeness, Strategy; Factor; WAG; Multicultural; Intercultural Pragmatics